Thermally enhanced biodegradation mechanisms of trichloroethene and benzene co-contaminants in groundwater: insights into microbial functional gene enrichment and biogeochemistry - Zhang, Zhuanxia; Ali, Mukhtiar; Wang, Qing; Coulon, Frederic; Song, Xin (Elsevier, 2025)
A series of thermally enhanced biodegradation (TEB) experiments at varying temperatures (15, 30 and 45 °C) were conducted to evaluate their effects on the biodegradation kinetics of trichloroethene (TCE) and benzene co-mingled contaminants using indigenous microbial consortiums. Results demonstrated that the highest TCE biodegradation rate, 0.35 μ mol L⁻¹ day⁻¹, with a half-life of 49 days, was observed at 30 °C, whereas the biodegradation of benzene was enhanced to a less extent. The functional gene analysis results revealed that increased tceA and tmoA genes contributed to enhanced TCE and benzene biodegradation at 30 °C, respectively. Additionally, the reduced vcrA and bvcA abundance and lack of effective electrons may attribute to the cis-1,2-dichloroethylene stalling and low concentration of ethene. Moreover, the biogeochemical analyses confirmed that elevated temperature promoted denitrification and sulfate reduction processes, which expedited methanogenesis, leading to the enhanced dechlorination of TCE. Additionally, the abiotic degradation of TCE facilitated by FeS, evidenced by acetylene and ethene detections, also contributed to the observed enhanced TCE degradation. The study shed lights on the role of temperature in enriching microbial functional gene and influencing biogeochemical conditions for the simultaneous anaerobic biodegradation of TCE and benzene. The findings demonstrated that optimized thermal treatments can effectively bioremediate chlorinated and aromatic hydrocarbons in groundwater.
Keywords: 4103 Environmental Biotechnology; 41 Environmental Sciences; Genetics; Strategic, Defence & Security Studies; 34 Chemical sciences; 40 Engineering